2011
DOI: 10.1007/s00122-011-1765-7
|View full text |Cite
|
Sign up to set email alerts
|

Extending the rapeseed gene pool with resynthesized Brassica napus II: Heterosis

Abstract: Hybrid breeding relies on the combination of parents from two differing heterotic groups. However, the genetic diversity in adapted oilseed rape breeding material is rather limited. Therefore, the use of resynthesized Brassica napus as a distant gene pool was investigated. Hybrids were derived from crosses between 44 resynthesized lines with a diverse genetic background and two male sterile winter oilseed rape tester lines. The hybrids were evaluated together with their parents and check cultivars in 2 years a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
53
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 19 publications
2
53
1
Order By: Relevance
“…The low seed yield in the IN inbred population was apparently attributable to introduction of several unfavorable alleles from B. oleracea, and this is not very uncommon for the inbred lines derived from interspecific crosses. For example, Girke et al (2012) found that resynthesized B. napus lines, on average, showed poor performance for seed yield; however, this type of materials can show good potential for high seed yield in hybrids. Among the three populations, the WS inbred population and its hybrid population yielded higher than the other two populations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The low seed yield in the IN inbred population was apparently attributable to introduction of several unfavorable alleles from B. oleracea, and this is not very uncommon for the inbred lines derived from interspecific crosses. For example, Girke et al (2012) found that resynthesized B. napus lines, on average, showed poor performance for seed yield; however, this type of materials can show good potential for high seed yield in hybrids. Among the three populations, the WS inbred population and its hybrid population yielded higher than the other two populations.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the value of utilizing allelic diversity of the allied Brassica species for increased heterosis in B. napus (Qian et al, 2005;Li et al, 2006;Zou et al, 2010;Girke et al, 2011Girke et al, , 2012Jesske et al, 2013;Li et al, 2014). For example, Zou et al (2010) observed a high level of heterosis in test hybrids while using germplasm diversified with the A genome of B. rapa and the C genome of B. carinata.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Turi et al (2010) found significant results of GCA (0.68) for genotype NUM120 and SCA (-1.41) for cross NUM113 x NUM105. Ahmad et al (2012), Girke et al (2012), Nasim and Farhatullah (2013) and Noor-Ul-Abideen et al (2013) assessed the significant effects of GCA and SCA for protein contents.…”
Section: Protein Contents (%)mentioning
confidence: 99%